2021
DOI: 10.1590/1518-8345.5180.3487
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, daytime sleepiness and sleep quality among technical-level Nursing students

Abstract: Objective: to evaluate the association of the burnout syndrome with daytime sleepiness and sleep quality among technical-level Nursing students. Method: a cross-sectional, analytical and quantitative study, conducted with 213 students from four technical Nursing courses in a city of Paraná, Brazil. Data collection was carried out using an instrument containing characterization information, the Maslach Burnout Inventory - Student Survey, the Epworth Sleepiness Scale and the Pittsburgh Sleep Quality Index. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
(51 reference statements)
0
5
0
Order By: Relevance
“… 49 Additionally, night shift workers commonly experience excessive daytime fatigue and somnolence that predispose them to higher risks EE and DP. 50 Despite these health hazards, the nature of shift work will be hard to modify as it is an integral part of the nursing profession to provide round-the-clock patient care. Therefore, it is vital to integrate important components such as sleep hygiene and psychosocial support into the nursing education curriculum to better equip young nurses in facing the impending challenges in their future careers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 49 Additionally, night shift workers commonly experience excessive daytime fatigue and somnolence that predispose them to higher risks EE and DP. 50 Despite these health hazards, the nature of shift work will be hard to modify as it is an integral part of the nursing profession to provide round-the-clock patient care. Therefore, it is vital to integrate important components such as sleep hygiene and psychosocial support into the nursing education curriculum to better equip young nurses in facing the impending challenges in their future careers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that nurses on more rotational shifts or night shifts were more likely to suffer from negative physical and psychological health impacts 49. Additionally, night shift workers commonly experience excessive daytime fatigue and somnolence that predispose them to higher risks EE and DP 50. Despite these health hazards, the nature of shift work will be hard to modify as it is an integral part of the nursing profession to provide round-the-clock patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Allen et al also found in their study with graduate students that sleep quality has more consistent relationship with burnout and might be more important than sleep duration in order to reduce burnout levels 40 . It is already known that a poor sleep quality is associated with higher levels of fatigue and exhaustion, and when it comes to graduate students, this can impact directly and negatively the student’s personal life and academic productivity 41 , 42 . Given that together with prolonged and chronic stress, the lack of energy and motivation can make students less interested in their studies and more prone to develop academic burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Also, daytime sleepiness and morning tiredness could all feed into the latency period at night. It is worth noting that these experiences (huge academic tasks, daytime sleepiness, and morning tiredness) are significant factors in the academic journey of the medical student as these will derail their energy, attention, and effort during the day, leading to burnout and other significant mental health challenges (Amaral et al, 2021). In effect, the medical student must pay close attention to these factors and employ strategies to manage them properly.…”
Section: Discussionmentioning
confidence: 99%